Hyponatremia in patients receiving parenteral nutrition: the importance of correcting serum sodium for total proteins. The role of the composition of parenteral nutrition in the development of hyponatremia. Issue 3 (March 2018) - Gómez-Hoyos, Emilia; Fernández-Peña, Silvia; Cuesta, Martín; Ortolá, Ana; Matía, Pilar; Pérez-Ferre, Natalia; De Luis, Daniel; Calle-Pascual, Alfonso; Rubio, Miguel; Runkle-De la Vega, Isabelle
Abstract Background/objectives Hyponatremia is the most common electrolyte disorder, and is associated with high-morbimortality rates. The true prevalence of hyponatremia in patients on parenteral nutrition (PN) is unknown, and the relationship between PN composition and development of hyponatremia has yet to be studied. Hypoproteinemia, a common finding in patients receiving PN, induces an overestimation of serum sodium (SNa) levels, when using indirect electrolyte methodology. Thus, SNa should be corrected for serum total protein levels (TP). The objective was to accurately determine the prevalence of hyponatremia (indirect SNa corrected for PT) and evaluate the relationship between the composition of PN and the development of hyponatremia. Subjects/methods Medical records of 222 hospitalized patients receiving total PN during a 7-month period were reviewed. Composition of PN, indirect SNa-mmol/l-, and SNa corrected for TP (SNa-TP)-mmol/l-, both upon initiation and during PN administration, were analyzed. Results Hyponatremia (SNa < 135 mmol/l) was present in 81% of subjects when SNa was corrected for TP, vs. 43% without correction (p = 0.001). In total 64% of patients that were eunatremic upon initiation of PN developed hyponatremia during PN administration, as detected by SNa-TP, vs. 28% as detected by uncorrected SNa (p < 0.001). There were no significant differences in volume, osmolarity, sodium or total osmols administered in PN between patients who developed hyponatremia and those who remained eunatremic. Conclusions A majority of patients receiving PN present hyponatremia, when indirect SNa levels are corrected for TP. The development of hyponatremia during PN is not related to the composition of the PN.